Mechanism of Suspended Kaolinite Particle Clogging in Porous Media During Managed Aquifer Recharge. Issue 5 (19th March 2019) - Ye, Xueyan; Cui, Ruijuan; Du, Xinqiang; Ma, Sijia; Zhao, Jingtong; Lu, Ying; Wan, Yuyu
Abstract: Managed aquifer recharge is an effective strategy for urban stormwater management. Chemical ions are normally retained in stormwater and groundwater and may accelerate clogging during the recharge process. However, the effect of water chemistry on physical clogging has not previously been investigated. In this study, we investigated the hydrogeochemical mechanism of saturated porous media clogging in a series of column experiments. The column was packed with river sand and added suspensions of kaolinite particles. Calcium chloride and sodium chloride are used as representative ions to study chemical effects. We found that an increase in ionic strength resulted in retention of kaolinite solids in the column, with a breakthrough peak of C / C 0 value of 1 to 0.2. The corresponding hydraulic conductivity decreased with increased solids clogging. Divalent cations were also found to have a greater influence on kaolinite particle clogging than monovalent cations. The enhanced hydrochemical‐related clogging was caused by kaolinite solids flocculating and increasing the deposition rate coefficient by 1 to 2 times in high ionic strength conditions. Three clogging mechanisms of kaolinite solids are proposed: surface filtration, inner blocking, and attachment. This study further deepens the understanding of the mechanisms of solids clogging during aquifer recharge and demonstrates the significance of ionic strength on recharge clogging risk assessments. Abstract : Article impact statement : The impacts of water chemistry including ionic strength and cation type on physical clogging of kaolinite particles were examined.